Competition, Contracts, and Creativity: Evidence from Novel Writing in a Platform Market - Wu, Yanhui; Zhu, Feng (Management Science, 2022)
A growing number of people today are participating in the gig economy, working as independent contractors on short-term projects. We study the effects of competition on gig workers’ effort and creativity on a Chinese novel-writing platform. Authors produce and sell their works chapter by chapter under a revenue-sharing or pay-by-the-word contract with the platform. Exploiting a regulation that induced a massive entry of novels in the romance genre but not other genres, we find that, on average, intensified competition led authors to produce content more quickly, whereas its effect on book novelty was weak. However, revenue-sharing books responded to competition substantially more than pay-by-the-word books, particularly regarding novelty. Moreover, the effect of competition on novelty is considerably stronger for books at earlier stages of the product life cycle. Finally, the platform increased the promotion of contracted books, which disproportionately favored pay-by-the-word books. We discuss the implications of these results for creative workers, platform firms, and policy makers in the gig economy. This paper was accepted by Anandhi Bharadwaj, information systems. Supplemental Material: Data and the online appendix are available at https://doi.org/10.1287/mnsc.2022.4329 .